Analysis of optical and thermal factors' effects on the transient performance of parabolic trough solar collectors. (February 2019) - Xu, Li; Sun, Feihu; Ma, Linrui; Li, Xiaolei; Lei, Dongqiang; Yuan, Guofeng; Zhu, Huibin; Zhang, Qiangqiang; Xu, Ershu; Wang, Zhifeng
Highlights: Transient model was built to analyze unsteady thermal behaviors of PTCs. It was validated with experiment data measured from a utility-scale loop of PTCs. Parametric studies were made to analyze essential impact factors. Abstract: Solar resources are inherently unsteady and their energy density on the earth is low. Thereby, when the solar energy is converted into thermal energy through concentrating the sunlight, how to predict the transient performance of parabolic trough solar collectors under the operating conditions is necessary for the steady useful output and the efficient use of the energy. So this paper describes a mathematical model of the transient thermal behaviors of parabolic trough solar collectors. Then, to validate this transient model, its numerical results are compared with the experimental data. These data were collected from a utility-scale loop of parabolic trough solar collectors. The comparison between the model predictions and the experimental data shows a consistent and reasonable agreement. Furthermore, the primary interest of this study is to determine how the temperature distributions of the absorber, the glass envelope and the heat transfer fluid evolve from initial conditions with specified optical and thermal parameters. Thus, this model is used to carry out parametric studies to make analyses of essential impact factors on transient behaviors of parabolic trough solar collectors. These factors include the temperature of the heat transfer fluid at the inlet, the initial conditions, and the optical efficiency. Moreover, this model has the function of continuous adjustment of the flow rate to satisfy the requirement of the temperature of the heat transfer fluid at the outlet according to varying boundary conditions. Hence, another analysis is performed to investigate transient processes when the flow rate is continuously adjusted at various DNI ramp rates.